Understanding of Speech Production in Cleft Lip/Palate: A Review - Yohana, Nelvi; Handoko, Handoko (Masyarakat Linguistik Indonesia Universitas Andalas, 2023)
A cleft lip is a disorder caused by the incomplete joining of the lips or palate during fetal development. This condition can result in a variety of physical impairments, speech impairments, and even psychological impairments that can affect a person’s life. Patients with cleft lip usually suffer from dental problems, speech problems, and breathing and hearing problems. This condition can certainly lead to emotional and social problems that require attention from various parties, including surgeons, dentists, speech therapists, and psychologists, essential. Patients with cleft disorders usually have an inability to produce speech sounds due to the insufficient amount of air pressure passing through the oral cavity. The severity of the disorder depends on various factors such as the intensity of the cleft, age at the surgery, and hearing loss. Early support and treatment can greatly improve patients’ quality of life. It is necessary to conduct comprehensive research to address the different issues associated with cleft lip/palate. This involves not only healthcare professionals, such as speech-language pathologists, surgeons, orthodontists, and pediatric dentists, but also communication experts, such as linguists, to develop effective treatments and strategies. This review article discusses the relationship between clefts and speech production, as well as the factors that play a role in improving the quality of life of patients with cleft. The article aims to provide a comprehensive overview of clefts, serving as a reference for dentists, surgeons, linguists, and other professionals who work with cleft patients.